Dynamic Antibody Response and Hybrid Immunity Following Multiple COVID-19 Vaccine Doses and Infection: A Case Study - Kanokudom, Sitthichai; Suntronwong, Nungruthai; Duangchinda, Thaneeya; Wanlapakorn, Nasamon; Poovorawan, Yong (Curēus (Palo Alto, CA), 2023)
This case study highlights the dynamic nature of the antibody response to SARS-CoV-2 in a vulnerable subject aged 70 years between 2021 and 2023. This individual had been vaccinated with six doses of the ancestral (Wuhan-Hu-1) COVID-19 vaccine and had a breakthrough infection 126 days after receiving Covovax™ (CO) as the sixth dose. The serostatus for total immunoglobulin specific to the receptor binding domain (total RBD Ig) changed from negative to positive following a two-dose CoronaVac (CV) vaccination, indicating a successful immune response. Booster doses, including AZD1222 (AZ), half-dose BNT162b2 (PF), and CO, increased the total RBD Ig levels, except for CV. The individual experienced a breakthrough infection by the Omicron BA.5 variant, leading to a substantial surge in total RBD Ig to over 105 U/mL. This generated sustained and extended antibody persistence, with the half-life of total RBD Ig lasting approximately 103.6 days. Furthermore, it has been observed that this breakthrough infection generated the highest neutralizing antibodies against BA.5, followed by XBB.1.5, BQ.1.1, and BA.2.75, respectively.